2006
DOI: 10.1007/s00213-005-0226-x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroactive steroids, negative affect, and nicotine dependence severity in male smokers

Abstract: DHEAS levels were inversely correlated with negative affect and craving measures, and may predict nicotine dependence severity. Allopregnanolone levels were positively correlated with cotinine levels, suggesting that this neuroactive steroid may be upregulated in smokers. Neuroactive steroids may represent novel smoking cessation agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 89 publications
3
35
1
Order By: Relevance
“…Interestingly, IV cocaine also stimulated significant increases in DHEA and cortisol that were similar in time course and magnitude to smoking a high-nicotine cigarette (Mendelson et al, , 2003. We have suggested previously that the significant nicotine-induced increases in cortisol and DHEA may contribute to the abuse-related effects of cigarette smoking (Mendelson et al, 2005) and DHEA has also been suggested as a potential medication for smoking cessation (Marx et al, 2006).…”
Section: Tolerance To Nicotine's Biological and Subjective Effectsmentioning
confidence: 58%
See 1 more Smart Citation
“…Interestingly, IV cocaine also stimulated significant increases in DHEA and cortisol that were similar in time course and magnitude to smoking a high-nicotine cigarette (Mendelson et al, , 2003. We have suggested previously that the significant nicotine-induced increases in cortisol and DHEA may contribute to the abuse-related effects of cigarette smoking (Mendelson et al, 2005) and DHEA has also been suggested as a potential medication for smoking cessation (Marx et al, 2006).…”
Section: Tolerance To Nicotine's Biological and Subjective Effectsmentioning
confidence: 58%
“…Although the role of cortisol in nicotine dependence is unclear, a decrease in cortisol after smoking cessation appears to predict a higher risk for relapse (al'Absi et al, 2004;Rasmusson et al, 2006). DHEA has recently been suggested as a medication to facilitate smoking cessation, in part because levels of its sulfated derivative, DHEAs, were inversely correlated with several measures of nicotine dependence and negative affect in smokers (Marx et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The intra-assay coefficient of variation (CV) is 4.7 percent, and the interassay CV is 8.4 percent. Plasma levels of ALLO were measured by gas chromatography-mass spectrometry (GC-MS) after separation of the steroids by high-performance liquid chromatography using previously published methods [43][44]. ALLO levels were identified based on their GC-MS retention time characteristics; the definitive structural identification of each neurosteroid is provided by its unique mass fragmentation pattern.…”
Section: Neurohormone Assaysmentioning
confidence: 99%
“…However, alcohol-dependent patients were almost all nicotine-dependent while controls were not. Although a previous study reported that cigarette smoking in abstinent alcohol-dependent subjects did not alter the pituitary-adrenal response to a pharmacological challenge (Anthenelli et al, 2001), a more recent study found that 3α,5α-THP levels may be up-regulated in smokers and dehydroepiandrosterone sulfate levels may predict nicotine dependence (Marx et al, 2006). Indeed, acute administration of nicotine alters pregnenolone, progesterone, 3α,5α-THP and 3α,5α-THDOC levels in rat brain and plasma (Porcu et al, 2003).…”
Section: Discussionmentioning
confidence: 92%